Inside AutoCAD® 2002 - Harrington, David; Burchard, Bill; Pitzer, David (Que, 2001)
This edition provides rock solid information on the latest changes and enhancements of the past two AutoCAD releases. The book guides you through the newest enhancements and shows you how to apply them to real projects. The great thing about this book is that it gets you up to speed fast and clearly outlines what is new from the previous versions. The CD-ROM has all the files to complete the tutorials. From Attributes to Xrefs, Inside AutoCAD 2002 details the features that put you on the fast track to AutoCAD success. Find out how to use dimensions, explore 3D modeling, learn how to plot, and learn about dozens of other features just waiting to be utilized.